2000
DOI: 10.3406/paleo.2000.4712
|View full text |Cite
|
Sign up to set email alerts
|

Annealing, distilling, reheating and recycling : bitumen processing in the Ancient Near East

Abstract: Throughout the prehistory and history of the Near East, natural petroleum tar or bitumen was commonly used for waterproofing, mastic, sealing, mortar, medicine, magic and even warfare. The people of ancient Mesopotamia manipulated this adhesive to lower its melting temperature in order to conserve fuel in an area where timber was a scarce resource. Not only was heat employed to change the chemistry of the bitumen to make it more workable, but the bitumen's chemistry was manipulated so less heat was required to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…51-53) show that bitumen reheating and reuse is common. It is worth noting that experiments by Schwartz and Hollander (2001) using bitumen from La Brea Tar Pits in Los Angeles showed that heating in excess of 72 h rendered the bitumen brittle and unusable. Indeed chemical and physical variation between seep bitumen can be considerable and thus not all bitumen will possess the 72 h threshold.…”
Section: Bitumen In Mesoamericamentioning
confidence: 99%
“…51-53) show that bitumen reheating and reuse is common. It is worth noting that experiments by Schwartz and Hollander (2001) using bitumen from La Brea Tar Pits in Los Angeles showed that heating in excess of 72 h rendered the bitumen brittle and unusable. Indeed chemical and physical variation between seep bitumen can be considerable and thus not all bitumen will possess the 72 h threshold.…”
Section: Bitumen In Mesoamericamentioning
confidence: 99%
“…The material we use is made of birch bark pitch, which is known to have been used as an adhesive substance in lithic tool technology from the Middle Palaeolithic onward in many parts of Eurasia 1216 , but also for recreational purposes 17,18 and as a cement for mending and sealing wood and ceramic vessels 19,20 . A variety of substances with similar properties, such as resins from a variety of coniferous trees 21–23 , natural bitumen 24,25 , as well as spinifex, chicle, and other plant gums 2628 , are also known to have been used in analogous ways in many parts of the world, but their ability to preserve ancient DNA remains to be tested. In this study, we investigate the relationship between Stone Age populations and cultural traits expressed in lithic technology in Scandinavia.…”
Section: Introductionmentioning
confidence: 99%
“…Bitumen can, of course, also be moulded to manufacture ornamental items such as beads, dice and gaming pieces [29, 61, 62] and the lumps from Sutton Hoo may be the fragmentary remains of small bitumen objects of this kind. Their distribution at the head and foot of the coffin places them close to the areas where the ivory gaming pieces in the burial were discovered, but the locations do not correlate well enough to infer an association: most of the ivory fragments were found near the shield and other objects along the west wall of the chamber, while the best preserved ivory gaming piece was found underneath the silver dish.…”
Section: Resultsmentioning
confidence: 99%